Cidade educadora: por que tornar-se uma? - Munhoz, Isabela Marin (2021)
The concept of the educating city emerged in the 1990s in Barcelona, Spain, where the first International Congress of Educating Cities was held, resulting in the Charter of Educating Cities. This charter refers to the city's intentionality and responsibility towards the education, promotion, and development of all its inhabitants, starting with children and young people, awakening a sense of responsibility and community by prioritizing the capacity for dialogue, confrontation, and solidarity. The central idea is that it is not only the school that educates, the city can intentionally educate in an informal way. The present research aims to conceptualize the educating city, its principles and possible impasses; to identify experiences of cities that are educating, and to point out ways for cities to become educating. The research is of an applied nature, the approach to the problem is qualitative and the technical procedure adopted is bibliographical research.